+0  
 
-1
175
1
avatar

All good here :^)

Guest Aug 29, 2017
edited by Guest  Aug 29, 2017
Sort: 

1+0 Answers

 #1
avatar+86583 
+1

 -6 + (14 + 2[60 - 9(1 + 3)]) =

-6 + (14 + 2 [60  - 9(4) ] ) =

-6 + (14 + 2 [ 60 - 36 ] )  =

-6  + ( 14  + 2 [ 24] )  =

-6 + ( 14 + 48 )  =

-6 + 62  =

56

 

(6^2 - 2^2) / 8  =

(36 - 4)  / 8  =

32 / 8 =

4

 

7/3 + 3 (3/4 - 2/3)^2  =

7/3 + 3 ( 9/12 - 8/12)^2 =

7/3 + 3 (1/12)^2  =

7/3 + 3 (1/44)  =

7/3 + 3/144  =

7/3 + 1/48   =   

[7 * 16 ] / [3 * 16]  +  1/48  =

[ 112] /[48] +  1/48 =

113 / 48

 

6/7 + 6(1/2 - 1/3)^2  =

6/7 + 6 ( 3/6 - 2/6)^2 =

6/7 + 6 (1/6)^2 =

6/7 + 6 (1/36) =

6/7 + 6/36 =

6/7 + 1/6 =

[ 6 * 6] / [ 6 * 7]  +  [ 1 * 7] / [ 6 * 7]  =

36 /42  + 7 /42  =

43 /42

 

 

cool cool cool

CPhill  Aug 29, 2017

29 Online Users

avatar
avatar
avatar
New Privacy Policy (May 2018)
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  Privacy Policy